Arte, iconoclastia e diritti umani - Maggiorelli, Simona (Il sogno della farfalla, 2016)
The destruction of works of art and of monuments in the Middle east by IS fundamentalists has been preceded by Christian iconoclasm, which, according to well-known archaeologists, byzantine historians and psychiatrists, has been the cruellest. Christian iconoclasm, in turn, was based on tianity and Neoplatonism interviewed, which was the cause behind the Eighth Century’s byzantine crisis. By reading Taliban iconoclasm and drawing a parallel with the destruction of artistic heritage which characterised Nazism and the war in ex-Yugoslavia, it may be highlighted how the actual destruction of works of art is linked to the manifest intention of erasing cultures that are open to dialogue, violating human rights, destabilizing, terrorizing, killing, to then also annulling memory. Jewish iconoclasm. The article outlines the genesis of ancient iconoclasm, highlighting how Christianity and Neoplatonism interviewed, which was the cause behind the Eighth Century’s byzantine crisis. By reading Taliban iconoclasm and drawing a parallel with the destruction of artistic heritage which characterised Nazism and the war in ex-Yugoslavia, it may be highlighted how the actual destruction of works of art is linked to the manifest intention of erasing cultures that are open to dialogue, violating human rights, destabilizing, terrorizing, killing, to then also annulling memory.